PENINGKATAN KUANTITAS DAN KUALITAS BATIK, ECOPRINT JOMBANG DENGAN INOVASI TEKNOLOGI MESIN DRYROOM INFRARED.: Peningkatan Kuantitas Dan Kualitas Batik, Ecoprint Jombang Dengan Inovasi Teknologi Mesin Dryroom Infrared. - Zuraidah, Safrin; Ichlas Wahid; Ilya Farida; Roosida Ully T, Liosten Rianna (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2025)
AbstractOemah Batik Nusantria, a batik business in Jombang, faces serious challenges due to the low qualityof its products, particularly batik and eco-print, compared to its competitors. The main problem stemsfrom the high humidity in Wonosalam, which slows down the fabric drying process by 1–3 days. Thiscondition reduces color quality, especially in natural eco-prints, and hinders productivity. Additionally,designs that are unappealing to younger generations and a limited number of artisans further restrictproduction capacity.The Community Empowerment Partnership Program (PKM) aims to improve thecompetitiveness of partners by offering innovative solutions. The technological innovationimplemented is an infrared dryroom machine, which has succeeded in accelerating the drying processof 12 pieces of fabric to 90 minutes (300% efficiency), while increasing productivity by up to 60% andmaintaining color quality. To address design issues, the PKM team provided training in motifinnovation using economical cardboard canting caps, resulting in five modern motifs that appeal tovarious groups. Training in natural and synthetic dyeing was also provided to improve quality andproduction capacity by up to 40%. This synergy demonstrates the role of academics in providingtechnological solutions that combine local wisdom to support the sustainability of the batik business inSumberjo village.Keywords: batik , eco-print, infrared, dryroom